Buddhadhamma with the Development of Thai Society in the 21st Century - Kamnerdthon, Jumrieang; Saegsin, Chamnian (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 10 No 2 (2018): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2018)
Academic article on “Buddhadhamma and the development of Thai society in the 21st century”, from the study of Buddhist teaching, Thai literature synthesis and research, aims to study Whether Buddhism is related to the development of Thai society or not and how. The study found that Buddhism is directly involved in the development of Thai society in the 21st century. According to the way of life of the Thai people in the 21st century has changed faster and more complicated than the past. Amid capitalism and economic competition Resulting in people in society having material values Focusing on self – interest Taking advantage of Lack of serious and continuous moral and ethical development. Resulting in an imbalance in both the mind and the object. It is accepted that the creation of people starts with the development of the mind. The study found that Buddhist doctrine is directly involved in the development of Thai society in the 21st century. Starting from before enlightenment was the Buddha Relationship between Buddhism and Thai society Compassion. The application of Buddhist principles in the development of Thai society as a basic foundation. The development is divided into 2 areas: (1) mental development means the development of people to have good mental quality, virtue, compassion, faith, endurance, concentration, persistence, mindfulness, generosity (2) The development of intelligence means knowing and understanding things as they really are. Be aware of the state of the world and life. The mind is free, do not fall under the power of lust, preconceptions and ignorance. The development of intelligence to know the causes of decay and how to create causes of prosperity in society.